1986
DOI: 10.1111/j.1439-0434.1986.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Enzyme Production of Erwinia carotovora ssp. atroseptica on Potato Tuber Tissue

Abstract: The elicitation of pathogenesis on potato tuber slices by 6 strains of Erwinia carotovora ssp. atroseptica was investigated by neutral red vital staining and has been compared with bacterial growth rate, penetration ability, enzyme production and enzyme spectrum. The induction of enzyme synthesis (particularly, of the extracellular polygalacturonase) elicites the rot attack on tuber tissue and this requires a sufficient bacterial density.Due to wound healing, the inductors of enzyme production are removed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many authors have reported that potato slices inoculated by Pectobacterium strains showed soft rot symptoms resulting of the secretion of various extracellular enzymes (Bain and Pérombelon 1988;Karlovsky et al 2008;Lapwood and Read 1985;Lapwood et al 1984;Pérombelon 2002;Terta et al 2010;Toth et al 2003;Weber and Wegener 1986), and that the pathogenicity of P. carotovorum and P. atrosepticum is known to be regulated by quorum sensing; a population density-dependent modulation of the bacterial phenotype (Barnard et al 2007;Swift et al 1996). The disease could be efficiently inhibited by biocontrol agents maintaining the pathogen population below the level required for symptom development.…”
Section: Discussionmentioning
confidence: 97%
“…Many authors have reported that potato slices inoculated by Pectobacterium strains showed soft rot symptoms resulting of the secretion of various extracellular enzymes (Bain and Pérombelon 1988;Karlovsky et al 2008;Lapwood and Read 1985;Lapwood et al 1984;Pérombelon 2002;Terta et al 2010;Toth et al 2003;Weber and Wegener 1986), and that the pathogenicity of P. carotovorum and P. atrosepticum is known to be regulated by quorum sensing; a population density-dependent modulation of the bacterial phenotype (Barnard et al 2007;Swift et al 1996). The disease could be efficiently inhibited by biocontrol agents maintaining the pathogen population below the level required for symptom development.…”
Section: Discussionmentioning
confidence: 97%
“…A successful defence of invading Erwinia carotovora (Ec) bacteria needs an early recognition of the pathogen by the host plant (Weber & Wegener, 1986). Unsaturated oligogalacturonates (OG) released from plant cell wall pectin by the action of pectate lyase (PL) enzymes, the major virulence determinant of Erwinia carotovora bacteria, elicit plant defence responses (Ryan, 1988).…”
Section: Introductionmentioning
confidence: 99%